Influence of the Implemented Management Systems on Risk-Based Thinking in Organizations – A Review - Alina MATUSZAK-FLEJSZMAN; Beata PALIWODA (Communications of International Proceedings, 2020)
The paper presents a discussion on the influence of implemented management systems such ISO 9001, ISO 14001 and ISO 45001 on risk-based thinking in organizations. The requirement to use a risk-based thinking in the organizations appeared with the entry into force of international standards based on so-called high level structure. Many organizations have introduced basic principles related to the identification of risks and opportunities resulting from the application of a risk-based thinking. However, in international ISO standards are included only requirements. This means that the management of an organization may use a risk-based thinking in various ways to identify risks and opportunities and appropriately manage areas where risks and opportunities emerge. The complexity of the methods of application depends on the organizational context, including the internal environment and maturity of processes and management system as a whole [Zhemchugova and Levshina, 2020]. The aim of this article is to show the influence of implemented management systems on risk-based thinking in organizations. This article indicates the requirements for the risk-based thinking as part of the quality, environmental and occupational health and safety management system. The possibilities of using the risk-based thinking in the organization within three areas of systemic management were presented.
Keywords: Risks; Opportunities; Risk-Based Thinking; Quality Management System; Environmental Management System; Occupational Health and Safety Management System.